ANALISIS PERAN KOMITMEN ORGANISASI DALAM MENINGKATKAN AKUNTABILITAS KINERJA MELALUI KOMPETENSI PEGAWAI DAN SISTEM PENGENDALIAN INTERNAL - Dian Mustika; Puji Lestari; Reva Meiliana; Nolita Yeni Siregar (Jurnal Riset Terapan Akuntansi, 2026)
The Bandar Lampung City Government's SAKIP score for 2023 decreased by 3.41 compared to 2022, indicating a decline in performance accountability. This study aims to examine the effect of employee competence and internal control systems on Government Agency Performance Accountability System, with organizational commitment as a moderating variable in the Bandar Lampung City Government. This study uses a quantitative approach with primary data obtained through questionnaires. The sampling technique uses purposive sampling with three criteria, collecting 45 respondents from 16 OPDs in the Bandar Lampung City Government. The data analysis technique used Partial Least Square - Structural Equation Modeling (PLS-SEM) with the WarpPLS 8.0 application. The results of this study indicate that Employee Competence and Internal Control Systems have a significant effect on Government Agency Performance Accountability and that Organizational Commitment is able to moderate the relationship between Employee Competence and Government Agency Performance Accountability. Meanwhile, Organizational Commitment unable to moderate the relationship between internal control systems and Government Agency Performance Accountability. Keywords: Employee Competence, Internal Control Systems, Organizational Commitment, Government Agency Performance Accountability System